Preliminary Study of Ecological Dredging Technology for the Three Gorges Reservoir - ZHOU Wang-min, LI Xiao-meng, TAN Hao-yue, LUO Ping-an, ZHAO Ke-feng, LU Shu-qiang (长江科学院院报, 2025)
[Objective] Traditional dredging methods for reservoir sedimentation can cause resuspension of sediments, leading to the release of nutrients, and then affect the water environment. Proposing a reasonable and feasible ecological dredging scheme is important to prevent water environmental pollution caused by sediment dredging, which is a fundamental requirement for the sustainable exploitation of reservoir sediments. To address the issues of sedimentation in the Three Gorges Reservoir and secondary water pollution caused by traditional dredging methods, this study focuses on typical sediment-accumulated river sections and explores ecological dredging technologies suitable for deep-water and complex environments. [Methods] This study comparatively evaluated the characteristics, applicability, and environmental friendliness of existing reservoir dredging technologies. Based on the segmented sedimentation characteristics of the Three Gorges Reservoir, it proposed an environmentally friendly ecological dredging technology suitable for the reservoir. Typical sediment-deposited river sections in Fuling and Zhongxian were selected as representative areas. A two-dimensional hydrodynamic-suspended sediment mathematical model was established to simulate the dredging effects under different dredging equipment, and an ecological dredging technical scheme for these areas was developed. [Results] The results showed that ecological dredging technology outperforms traditional methods in precision control, pollution prevention, and resource utilization. The study recommended using pneumatic dredging for the near-dam section, pneumatic or jet dredging for the middle section, and pneumatic or eco-friendly cutter suction dredging for the upper section and fluctuating backwater area. Simulations indicated that pneumatic dredging had the least impact on suspended sediment concentration and diffusion. Based on the simulation results, comprehensive dredging recommendations were proposed, including equipment selection, construction timing, residual water treatment, and sediment resource utilization. [Conclusion] The ecological dredging scheme proposed in this paper can provide a reference for ensuring the storage capacity of the Three Gorges Reservoir and its long-term effective use, as well as sustaining comprehensive benefits. It shows strong potential for promotion and practical engineering application value.